Optimization of growth and survival of whiteleg shrimp (Litopenaeus vannamei) postlarvae through dietary variation: A study of physiological and microbiological responses - Izwar, Akmal; Nugrahawati, Anis; Hakim, Syahirman; Irfannur, Irfannur; Putra, Dani Pratama; Azhar, Rossy; Radhi, M (Acta Aquatica: Aquatic Sciences Journal, 2025)
The whiteleg shrimp (Litopenaeus vannamei) is a prominent species in global aquaculture due to its resilience to environmental fluctuations and high growth potential. The success of the larval phase is critically determined by feed quality and the stability of the culture environment. This study comparatively evaluated the efficacy of various feed types on the performance of Litopenaeus vannamei postlarvae. A comparison was made between live, frozen, and preserved natural feed (Artemia sp.) and formulated pellet feed in terms of growth, survival rate, and Vibrio bacteria abundance. The results highlighted that frozen Artemia sp. (P2) was significantly superior to other treatments. Postlarvae fed frozen Artemia sp. exhibited the highest growth (length and absolute weight) and survival rate, reaching 78.67%, significantly surpassing the pellet-fed group (K1) with a survival rate of only 60.67%. Furthermore, the Vibrio bacteria abundance in the frozen Artemia sp. fed group was also relatively low compared to the pellet-fed group (13.33 CFU mL⁻¹). Although live and preserved Artemia sp. yielded better results than pellet feed, frozen Artemia sp. remains the most effective feed choice for optimizing early-stage L. vannamei aquaculture. Keywords: Artemia sp.; Feed; Litopenaeus vannamei; Postlarvae; Vibrio sp.